Impact of Transparency and Accountability on Trust and Intention to Donate Cash Waqf in Islamic Microfinance Institutions - Zulfikar Ali Ahmad; Rusdianto Rusdianto (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Research examining the intention of cash waqf in Islamic Microfinance institutions remain more paucity of evidence. To the best of the authors' knowledge, previous studies have still been silent on exploring the intention of cash waqf in the context of Baitul Maal wat Tamwil (BMT). Dealing with this issue, this study examines the impact of transparency and accountability perception on trust and intention to donate cash waqf in Islamic Microfinance Institutions. This study employed a survey in the form of a questionnaire to obtain the required data from 303 waqif (people who donate cash waqf) both at BMT and another nazhir waqf around the island of Java, Indonesia. Furthermore, the data were analyzed using Structural Equation Model-Partial Least Square (SEM-PLS) in two stages, i.e., measurement models and structural models. The results of data analysis portrayed that the perception of transparency provided a significant impact on trust and intention to donate cash waqf in Islamic finance institutions. It was also depicted that the level of trust positively influenced the intention to give cash waqf in Islamic finance institutions. These results offer significant contributions as fruitful insights to strengthen the transparency and accountability of Islamic microfinance institutions, particularly Baitul Maal wat Tamwil (BMT) in Indonesia.